The Effectiveness of Papua’s Special Autonomy Fund Policy in Improving the Welfare of Indigenous Communities - Isak Klafle; Dian Ferriswara; Ulul Albab; Sapto Pramono (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the effectiveness of the Papua Special Autonomy policy in improving the welfare of indigenous communities by reviewing the achievement of policy objectives, integration and coordination between institutions, and policy adaptation to the socio-cultural conditions of the local community. The approach used is qualitative with the Qualitative Secondary Analysis (QSA) method, utilizing various secondary data sources such as policy documents, government reports, and relevant research and academic journals. The results of the study indicate that the Papua Special Autonomy policy was designed as an affirmative policy aimed at accelerating regional development, improving community welfare, and recognizing the rights of indigenous communities. This policy has produced several positive results, especially in increasing regional fiscal allocations, developing infrastructure, and expanding community access to education and health services. In addition, the establishment of special institutions such as the Papuan People's Assembly provides space for the representation of indigenous people's culture in the regional government system. However, the study also shows that the Special Autonomy policy faces several challenges, including suboptimal inter-institutional coordination, limited institutional capacity of local governments in managing Special Autonomy funds, and the incomplete integration of indigenous socio-cultural values ​​in the planning and implementation of development programs. Therefore, strengthening policy governance, increasing accountability in fund management, and expanding indigenous community participation are crucial factors in enhancing the effectiveness of Papua's Special Autonomy policy. This research provides theoretical contributions to public policy development, particularly in the context of implementing asymmetric decentralization and culture-based development policies.